Response to the Round Table on Selling Paris: Property and Commercial Culture in the Fin-de-siècle Capital - YATES, ALEXIA (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2017)
Alexia Yates responds to comments on her award-winning book, Selling Paris: Property and Commercial Culture in the Fin-de-siècle Capital.